Rhabdomyolysis following status epilepticus with hyperuricemia: A case report and literature review. Issue 26 (June 2018) - Wang, Lingxing; Hong, Shanyan; Huang, Honghong; Yang, Meili
Abstract: Rationale: Rhabdomyolysis owing to status epilepticus (SE) can be life-threating, with acute kidney injury (AKI) the most serious complication; therefore, early recognition of the risk factors is important. Hyperuricemia after epileptic seizures has been reported, and severe hyperuricemia can lead to acute renal function damage. Patient concerns: We present the case of a 21-year-old man hospitalized for SE, who had especially high level of blood uric acid (UA) at initial presentation. Diagnosis: The patient was diagnosed with rhabdomyolysis due to SE. Interventions: The patient was treated with hydration and bicarbonate therapy. But he developed acute kidney failure (AKF) and hemodialysis was performed. Outcomes: After hemodialysis, his symptoms disappeared and laboratory data returned to normal. Lessons: Hyperuricemia after SE might indicate severe muscle damage or reduced clearance of metabolites, and could be a risk factor for kidney dysfunction, especially with rhabdomyolysis. To our knowledge, this is the first report of rhabdomyolysis following SE with hyperuricemia.